Becoming A Unionized Workers: Exploring the Benefits and Hidden Challenges : Becoming A Unionized Workers: Exploring the Benefits and Hidden Challenges - Ismail, Fadillah; Nesreen Ibrahim Owaida, (Human Sustainability Procedia, 2023)
This article discussed about the concept of trade union around the world including Malaysia. In order to gain knowledges about trade union concepts, the author has reviewed the previous articles to support the objectives which to determine the concept of trade union, identifying the types of trade union, and elaborating the pro and cons of trade union. Most part of this article show the current trend of trade union in Malaysia which the number of members trade union has started to grow in a slower pace compared to other countries. There are several main topics being highlighted and being discussed in this study. First, the article explains the definition of trade union. There are a lot of definition that author found and its shows that the definition are the same but the law and regulation are different depending on the country they are established. Other than that, the article also mentions the function and the importance of trade union for workers in Malaysia. The acts being implied are depend on the situation and issues being brought up by the member of the unions. Next, there are several types of trade union in Malaysia being brought up in this article such as the public sector unions, private sector unions and employer union. On the other hand, the pros and cons of trade union also being elaborated in this article. The list of challenges also has discussed on this article where the challenges make the movement of trade union are weak and impact the number of members in the trade union. Lastly, there are also several recommendations being made to ensure that workers are interested to join the unions so that they know their rights when working for the industries. In other word, the recommendation has indirectly promoted the trade union to the people.